Síntese, caracterização e estudos biológicos de complexos de paládio(II) e platina(II) contendo tióis - Lacerda, Meiry Leandra de (2023)
The rational synthesis of metal-based drugs has been an area of vigorous research since the introduction of cisplatin as the first platinum drug employed in the treatment of cancer. Currently there are several metal complexes available as drugs, but the search for new drugs that are safer and more efficient than those already introduced in clinical practices, as well as in the use of these in the treatment of diseases that there is little or no treatment option available is growing. In the master's thesis, the synthesis and characterization of eight new palladium or platinum complexes of the type [Pd(L1-L4)2(en)] 1-4, [Pd(L5)(en)] 5, [Pt(L1 and L4)2(en)] 6-7 e [Pd(L3)2(fen)] 8 were carried out, being L the ligands 2-thioxotiazolidine-4-one (L1), 2-thioracil (L2), 5-Amino-1,3,4-thiadiazol-2-thiol (L3), 4-amino-6-hydroxy-2-mercaptopyrimidine (L4) and 2-mercaptopyridine-3-carboxylic acid (L5). All complexes were characterized by elemental analysis techniques (CHNS and/or CHN), molar conductivity, infrared spectroscopy (IR, as well as 1H and 13C NMR nuclear magnetic resonance. Additionally, complexes 1, 2, 3 and 5 were also characterized by electrospray ionization mass spectroscopy (HRESIMS). The complexes obtained are neutral (non-electrolytes) with the respective ligand coordinated to the metal ion in a monodentate way through the sulfur atom after deprotonation, except in the case involving complex 5, whose ligand coordinated with the metal ion in a bidentate manner via oxygen and sulfur atoms, after both undergo deprotonation. Additionally, the elemental and IV analysis data allowed us to infer those complexes 1, 2, 4, 5 and 7 are monohydrated. Subsequently, the compounds were investigated in tumor and normal cell lines and showed no activity. However, when they were analyzed against resistant strains of Campylobacter jejuni, some good results were observed, especially for complex 1 and its respective ligand (L1). Thus, biological studies have revealed that these compounds do not have a generic toxicity and may be useful in the development of antibacterial drugs.